Un roman néo-gothique : The Three Impostors d’Arthur Machen (1895) - Claire Wrobel (Cahiers Victoriens et Edouardiens)
Although he didn’t refer to a well-defined « Gothic » genre, Arthur Machen, in his 1895 novel, took up many elements which had by then become traditional. Medieval torture instruments and haunted Celtic forests no longer breed fear, but are used with excess and with parodic distance. The novel reflects the evolution of Victorian Gothic, setting tales of terror and horror in the here and now of fin-de-siècle London. The contemporary threats of New Women and democratization are casually brushed aside, but Machen fully draws upon the anxiety generated by the possibility of reversion opened up by the theory of evolution and explored by anthropologists and criminologists. Moreover, he breaks the original systematic association of « Gothic » and « barbaric » with « medieval » in order to include the refined cruelties and mysteries of pagan rites in his abject visions. In a final twist, he sets a barbaric scene in a decaying mansion meant to embody the eighteenth century, thus « gothicizing » the age of enlightenment and urbanity.